Individual size distributions across North American streams vary with local temperature. (12th September 2021) - Pomeranz, Justin P. F.; Junker, James R.; Wesner, Jeff S.
Abstract: Parameters describing the negative relationship between abundance and body size within ecological communities provide a summary of many important biological processes. While it is considered to be one of the few consistent patterns in ecology, spatiotemporal variation of this relationship across continental scale temperature gradients is unknown. Using a database of stream communities collected across North America (18–68°N latitude, −4 to 25°C mean annual air temperature) over 3 years, we constructed 160 individual size distribution (ISD) relationships (i.e. abundance size spectra). The exponent parameter describing ISD's decreased (became steeper) with increasing mean annual temperature, with median slopes varying by ~0.2 units across the 29°C temperature gradient. In addition, total community biomass increased with increasing temperatures, contrary with theoretical predictions. Our study suggests conservation of ISD relationships in streams across broad natural environmental gradients. This supports the emerging use of size‐spectra deviations as indicators of fundamental changes to the structure and function of ecological communities. Abstract : We constructed individual size distributions (ISDs) for aquatic macroinvertebrate communities across streams in the National Ecological Observation Network, to test how temperature controls biomass distributions within communities. We found that ISDs became steeper (e.g., relatively fewer large body sizes compared with small body sizes), but that community biomass increased across a mean annual air temperature gradient which spanned 29°C. The variation in ISD exponents we observed is consistent with the expectation that size spectra represent a stable pattern of community structure, and that strong deviations from this pattern may be used to monitor fundamental changes to the structure and function of ecological communities.